Energy efficient Parallel Optical Burst Switching (POBS) networks - Zaiter M.J. (Maxwell Science Publications, 2023)
Greening the Internet has recently become one of the main challenges for the research community due to economic and environmental reasons. In this context, optical technology can offer an energy efficient solution. As such it is interesting to examine Optical Burst Switching (OBS) network that provides an avenue for reducing energy consumption by significantly reducing the amount of header processing in the core switch. A variant of OBS, which is known as Parallel Optical Burst Switching (POBS), takes this concept further by transmitting bursts in two dimensions: the wavelength dimension and the time dimension. Consequently, this study investigates the power consumption in both the OBS and POBS technologies when used in the core network. The simulation results show that in the core network, the use of POBS can provide significant saving in energy as compared to the use of OBS. Furthermore, the use of POBS can lower the power consumption and the number of packets dropped in the network when appropriate parameter settings are used, particularly the burstification time and waveband granularity. © Maxwell Scientific Organization, 2014.